Inorganic constituents in surface runoff from urbanised areas in winter: the case study of the city of Brest, Belarus - Ina Bulskaya; Aliaksandr Volchek (Oceanologia, 2014)
The aim of this paper was to study the inorganic constituents of snow and snowmelt surface runoff in a case study of the city of Brest and to indicate components that could pose a threat to the environment. Samples of snow and snowmelt runoff were analysed for the following parameters: total suspended solids, pH, the contents of nitrate, phosphate and ammonium ions, and of heavy metals. The concentrations of most of these pollutants were higher in the snowmelt runoff than in snow. The concentrations of pollutants in the snowmelt surface runoff exceeded the levels established by national regulations (maximum permissible concentrations).